The acceptability and feasibility of an anxiety reduction intervention for emergency department patients with non-cardiac chest pain. Issue 1 (2nd January 2017) - Webster, Rosie; Thompson, Andrew Robert; Norman, Paul; Goodacre, Steve
Abstract: Despite good physical prognosis, patients who receive a diagnosis of non-cardiac chest pain (NCCP) may experience persistent pain and distress. While cognitive-behavioural interventions have been found to be effective for this group, they are difficult to deliver in busy emergency department (ED) settings. Addressing the acceptability and relevance of self-help interventions is an important initial step in addressing this need. This study sought to examine the acceptability and relevance of an evidence-based self-help intervention for ED patients with persistent NCCP and anxiety. Patient (interviews: N  = 11) and specialist chest pain nurse (focus group: N  = 4) views on acceptability and feasibility were examined. Data were analysed using thematic analysis. Patients and nurses reported that there was a need for the intervention, as stress and anxiety are common among patients with NCCP, and provision of psychosocial support is currently lacking. Both patients and nurses reported that the intervention was relevant, acceptable, and potentially useful. Some changes to the intervention were suggested. Nurses reported that the intervention could be used within the existing staff resources available in an ED setting. This study represents an important first step towards developing a brief self-help intervention for ED patients with NCCP and anxiety. Further research should seek to determine the efficacy of the intervention in a pilot trial.